2019
DOI: 10.3390/ijms20174070
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Effects of IL-4 on IL-17A-Mediated Enhancement of Epidermal Tight Junction Function

Abstract: Atopic dermatitis (AD) is the most common chronic and relapsing inflammatory skin disease. AD is typically characterized by skewed T helper (Th) 2 inflammation, yet other inflammatory profiles (Th1, Th17, Th22) have been observed in human patients. How cytokines from these different Th subsets impact barrier function in this disease is not well understood. As such, we investigated the impact of the canonical Th17 cytokine, IL-17A, on barrier function and protein composition in primary human keratinocytes and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 36 publications
0
22
0
1
Order By: Relevance
“…A T H 17 cytokine, IL-17A, decreases synthesis of tight junction proteins and degradation of filaggrin monomers (Yuki et al 2016), suggesting a vicious cycle between T H 2 and T H 17 sensitization and skin barrier dysfunction. Another study reported that IL-17A enhances the formation of tight junction proteins and barrier function (Brewer et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A T H 17 cytokine, IL-17A, decreases synthesis of tight junction proteins and degradation of filaggrin monomers (Yuki et al 2016), suggesting a vicious cycle between T H 2 and T H 17 sensitization and skin barrier dysfunction. Another study reported that IL-17A enhances the formation of tight junction proteins and barrier function (Brewer et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 is thought to have a number of protective roles in the skin, including enhancing production of antimicrobial peptides, such as lipocalin 2 and b-defensin, as well as neutrophil recruitment (Guttman-Yassky and Krueger, 2017). More recently, IL-17A has also been shown to enhance tight junction (TJ) barrier function in primary human keratinocytes (Brewer et al, 2019). Collectively, these actions likely contribute to the observation made by Sirobhushanam et al (2020) that none of their six subjects with PS were colonized with S. aureus.…”
Section: S Aureus Skin Colonizationmentioning
confidence: 93%
“…Ustekinumab, a monoclonal antibody targeting IL-12 and IL-23 that is FDA-approved to treat PS, has also shown some benefit for the treatment of LE (van Vollenhoven et al, 2018). This might seem surprising based on its inhibition of the IL-17 pathway, which one might predict would further aggravate skin barrier dysfunction and promote S. aureus colonization in LE (Brewer et al, 2019). Although IL-17 has been shown to be modestly elevated in LE, there is not much evidence that this is relevant for LE pathogenesis (Martin et al, 2014).…”
Section: Future Therapeutic Approachesmentioning
confidence: 99%
“…Specifically, the enhancement of barrier function was measured by transepidermal electrical resistance (TEER), and tight junction formation was demonstrated by expression of the protein claudin-4. IL-4, as a key cytokine of allergic inflammation, again blocked these effects [ 18 ].…”
Section: Effects Of a Basic Skin Therapy As A Primary Prevention Measurementioning
confidence: 99%